Primary succession of Bistorta vivipara (L.) Delabre (Polygonaceae) root‐associated fungi mirrors plant succession in two glacial chronosequences. (4th March 2015) - Davey, Marie; Blaalid, Rakel; Vik, Unni; Carlsen, Tor; Kauserud, Håvard; Eidesen, Pernille B.
Summary Glacier chronosequences are important sites for primary succession studies and have yielded well‐defined primary succession models for plants that identify environmental resistance as an important determinant of the successional trajectory. Whether plant‐associated fungal communities follow those same successional trajectories and also respond to environmental resistance is an open question. In this study, 454 amplicon pyrosequencing was used to compare the root‐associated fungal communities of the ectomycorrhizal (ECM) herb Bistorta vivipara along two primary succession gradients with different environmental resistance (alpine versus arctic) and different successional trajectories in the vascular plant communities (directional replacement versus directional non‐replacement). At both sites, the root‐associated fungal communities were dominated by ECM basidiomycetes and community composition shifted with increasing time since deglaciation. However, the fungal community's successional trajectory mirrored the pattern observed in the surrounding plant community at both sites: the alpine site displayed a directional‐replacement successional trajectory, and the arctic site displayed a directional‐non‐replacement successional trajectory. This suggests that, like in plant communities, environmental resistance is key in determining succession patterns in root‐associated fungi. The need for further replicated study, including in other host species, is emphasized.